Proceedings of the Inter-Centre meeting on germplasm health and movement, 23-25 October 1990, IBPGR HQ, Rome, Italy - Frison, Emile A.; International Board for Plant Genetic Resources (1991)
The meeting was held in Rome from 23 to 25 October 1990 and was attended by representatives of CIMMYT, CIP, IBPGR, ICARDA, ICRISAT, IITA and IRRI (see list of participants in Appendix I). A representative of FAO attended the first session of the meeting to provide an opportunity for an interaction between the Plant Protection Service of FAO and the participants from the different Centres (see programme attached in Appendix II). Dr N.A. van der Graaff, Chief, Plant Protection service, presented an outline of the major activities of the Service. In order to familiarize each other with current activities, representatives of each of the Centres presented a paper describing how, from a phytosanitary point of view, germplasm is handled in their respective Centre. The full papers presented will be given at the end of this report. This was followed by informal discussions on a number of relevant topics (see Appendix II) and led to the elaboration of recommendations and the planning of joint activities. A questionnaire to be addressed to all Centres holding plant genetic resources collections, was developed by the meeting to assemble data on germplasm health in the IARCs (see Appendix III). IBPGR will prepare a project proposal and seek complementary funding for some joint activities of the IARCs on germplasm health.